Dysregulation of lncRNA–miRNA–mRNA Interactome as a Marker of Metastatic Process in Ovarian Cancer - Irina V. Pronina; Leonid A. Uroshlev; Alexey A. Moskovtsev; Danila M. Zaichenko; Elena A. Filippova; Marina V. Fridman; Alexey M. Burdennyy; Vitaly I. Loginov; Tatiana P. Kazubskaya; Nikolay E. Kushlinskii; Alexey A. Dmitriev; Eleonora A. Braga; et al. (Biomedicines, 2022)
Ovarian cancer (OC) is one of the most common types of cancer among malignancies of the female reproductive system. This pathology is asymptomatic until advanced stages and has a poor prognosis. Our study aimed to search for lncRNA–miRNA–mRNA competing triplets that promote ovarian tumorigenesis. For this purpose, we analyzed tumor samples from the TCGA database and verified the results experimentally in a set of 46 paired samples of tumor and matched histologically unchanged ovarian tissues from OC patients. The list of RNAs selected in silico for experimental studies included 13 mRNAs, 10 lncRNAs, and 5 miRNAs related to epithelial–mesenchymal transition and angiogenesis. We evaluated the expression of these RNAs by qRT-PCR and assessed the correlation between levels of miRNAs, mRNAs, and lncRNAs. Sixteen significant triplets were revealed, in some of which, e.g., OIP5-AS1–miR-203a–c-MET and OIP5-AS1–miR-203a–ZEB2, both lncRNA and mRNA had sites for miR-203a direct binding. Transfection of the OVCAR-3 and SKOV-3 cell lines with the miR-203a mimic was used to confirm the novel links of miR-203a with ZEB2 and c-MET in OC. These connections suggest that the interactomes have the potential for diagnostics of metastasis at early onset.